Postoperative Outcome after Coronary Artery Bypass Grafting in Chronic Obstructive Pulmonary Disease - Hélène Manganas; Yves Lacasse; Stéphanie Bourgeois; Jean Perron; François Dagenais; François Maltais (Canadian Respiratory Journal)
BACKGROUND: It is uncertain if the presence and severity of airflow obstruction in chronic obstructive pulmonary disease (COPD) is predictive of surgical morbidity and mortality after coronary artery bypass grafting (CABG).